Impact of the COVID-19 pandemic on prenatal, diabetes and medical appointments in the Brazilian National Health System - Luiz Alexandre Chisini; Eduardo Dickie de Castilhos; Francine dos Santos Costa; Otávio Pereira D'Avila (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objectives: The purpose of this study was to describe the impact of the COVID-19 pandemic on Primary Health Care in Brazil. Methodology: This retrospective ecological study was carried out using Brazilian municipality data obtained from the information systems of the National Public Health System. The outcomes were medical appointments, prenatal procedures and diabetes care. The exposure variable was the occurrence of the COVID-19 pandemic, based on the first case reported in Brazil. Multilevel mixed-effects negative binomial regression was used to analyze the association between the number of procedures per 10,000 inhabitants and COVID-19. Results: Data from 5,564 Brazilian municipalities were included in the present study. Regarding medical appointments, the largest reduction occasioned by the pandemic occurred in May (IRR = 0.27, 95%CI 0.24 - 0.30). Prenatal procedures were reduced by 65% (IRR = 0.35, 95%CI 0.32 - 0.38), also in May. In addition, diabetes care saw the biggest reductions in April 2020 (IRR = 0.24, 95%CI 0.11 - 0.53) and May 2020 (IRR = 0.19, 95%CI 0.09 - 0.43). From February to December 2020, the pandemic had a significant effect on the total number of procedures evaluated. Conclusion: The findings showed a reduction in prenatal procedures, diabetes and medical consultations performed in Brazil's Primary Health Care, following the onset of the COVID-19 pandemic.